Development of Learning Module Reading Al-Qur’an Writing in Basic State School Rogomulyo 02 Semarang - Af'idah, Af'idah; Miftahuddin, Miftahuddin; Rohman, Taufiqur (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2020)
This research is motivated by the unavailability of teaching materials module for students. This research is a research and development, which the aims to produce a product of teaching materials such as Literacy Al-Qur'an Module effectively and efficiently. The subjects of this study were 23 fifth grade students of SD Rogomulyo 02 Kaliwungu District and accompanied by two validation experts. The data collection techniques used are observation, interviews, and test (Pretest and Posttest). The method for developing of literacy Al-Qur'an module uses Research and development steps developed by Borg and Gall. This steps are consist of 1) preliminary research, 2) product design, 3) validation, 4) product application, and 5) analysis.The results of this study indicate that, literacy al-Qur'an modules compiled by researchers, can improve learning achievement from the averages value of students above the KKM (Minimum completeness criteria). The conclusion is based on the processing of pre-test data of 64.52 and post-test of 77.86 using Paired Samples T-Test data resulting in an average correlation data of 0.806 and a significance value of 0,000. The results of the calculation of Paired Samples T-Test found the value of Sig. (2 tailed) is 0,000 ˂ 0.05, then H0 is rejected and Ha is accepted. Thus it can be concluded that there is an influence on using of literacy al-Qur'an module for students, it's proven any differences in the average between pre-test and post-test results of students or have comply the KKM (Minimum completeness criteria) in schools.